Taking your library career to the next level : participating, publishing, and presenting - Hibner, Holly; Kelly, Mary (2017)
"Taking Your Library Career to the Next Level: Participating, Publishing, and Presenting helps librarians establish a brand and name recognition in their area of expertise, suggesting how to write winning proposals for both publication and presentation and places to publish. In addition, it covers how to conquer fears of public speaking and how to make presentations more dynamic. As professional development is important in most library settings to earn or maintain credentials, this book helps academic librarians look for opportunities to earn tenure, also helping special librarians look for ways to focus their training on a narrow subject area. Regardless of their reason for looking for professional development opportunities, librarians of all types will find satisfaction in contributing to the profession at a higher level. Participating in professional conversations and decision-making that impacts others in the field, and sharing knowledge through publishing and presenting are great ways to become better librarians. Helps librarians establish an area of specialty and generate name recognition in their sub-field ; provides guidance on the writing process and publishing opportunities, also touching on places to present material. Includes guidance on establishing a brand, writing successful proposals, and being a dynamic speaker" -- Provided by publisher.
Keywords: Library science -- Vocational guidance; Library science -- Vocational guidance